Status of Food and Nutrition Security among Smallholder Farmers in Selected Districts of Eastern Uganda: A Cross-Sectional Study - Evas, J Tibagonzeka; Florence, L Kiyimba; Shamim, W Birungi; Jenifer Apil; Julius Wambete; John Sembera; George Makumbi; Grace Babirye; John Yawe; Peter Atekyereza (Journal of Food Innovation, Nutrition, and Environmental Sciences, 2025)
Food and Nutrition Security (FNS) remain critical concerns for smallholder farmers in Sub-Saharan Africa. This study looked at the food and nutrition situation of smallholder farmers in three selected districts of Kamuli, Buyende, and Pallisa in Eastern Uganda. A cross-sectional, mixed-methods approach was employed involving 647 smallholder households and 893 children aged 6–59 months. Food security was evaluated using four indicators: Household Dietary Diversity Score (HDDS), Food Consumption Score (FCS), Individual Dietary Diversity Score (IDDS), and Minimum Dietary Diversity (MDD) for a subsample of 308 children aged 6–23 months. Data were collected through dietary recalls, food frequency questionnaires, anthropometric assessments (Mid Upper Arm Circumference [MUAC] and Weight for Height Z-Scores [WHZ]), and market-based food price analysis. Qualitative insights were obtained from focus group discussions and key informant interviews. Results showed that, among households, 75.9% consumed fewer than three meals daily, and 32.5% exhibited low dietary diversity. The mean FCS was 28.8, indicating borderline food consumption. Among all children, 56.9% had inadequate dietary diversity (IDDS < 4), while 60.3% of those aged 6–23 months failed to meet the MDD standard. Overall, 15% of children were acutely malnourished, with Buyende district reporting the highest burden. Cost-effectiveness analysis identified cassava, sweet potatoes, sim-sim, and silverfish (mukene) as affordable, nutrient-rich foods. Participation in farmer groups was associated with better dietary outcomes. Food insecurity in the three selected districts of Eastern Uganda is multidimensional, affecting both the quantity and quality of diets. Locally tailored, nutrition-sensitive agricultural strategies are essential for improving child health and household resilience.